Toxicity assessment of Phlogacanthus thyrsiflorus, a traditionally used anthelmintic plant of India - Khirod Deori; Amar Deep Soren; Arun K. Yadav (SpringerOpen, 2023)
Abstract Background The leaves of Phlogacanthus thyrsiflorus are used as an anthelmintic remedy by the tribes of upper Assam. This study evaluates its toxic effects in laboratory bred mice and rats. Mice were orally dosed for 5 days, whereas rats were dosed for 28 days and variations in behaviour, feeding habits and blood parameters were recorded. The vital organs were processed for histopathology to observe any alternations from normal architecture. Results No mortality or adverse toxic effects were manifested in this assessment. Evaluated parameters, namely feeding behaviour, body weights and relative organ weights, appeared to be similar to the control animals. Also, the haematological and serum biochemical parameters and histopathological studies revealed normal results. Conclusions The study indicates that P. thyrsiflorus may not be capable of causing toxic effects in mice and rats, and hence, its traditional use as an anthelmintic could be continued. However, other studies to further validate this may be carried out.